Makanan Sattvika dan Pengaruhnya Terhadap Kesehatan dan Karakter - Ayu Veronika Somawati; Komang Surya Adnyana (UHN IGB Sugriwa Denpasar, 2020)
Being born as a human is a virtue in Hinduism, because among all living things only humans are gifted with the ability to think and distinguish good and bad deeds, and can help themselves from repeated births and deaths towards the ultimate goal of Hinduism. itself namely